Attachment Styles, Perceived Stress and Social Support in a Malaysian Young Adults Sample - Khodarahimi, Siamak; H. M. Hashim, Intan; Mohd Zaharim, Norzarina (Ubiquity Press, 2016)
The purpose of this research was to examine the validity of an adult attachment style questionnaire, to understand the relationships between the type of attachment style in relation to self-perceived stress and social support, and to investigate the influence of gender, ethnicity and religion on the above constructs. The participants were 308 university students from Malaysia. A demographic questionnaire and three self-report inventories were administrated in this study. The data indicated that the Relationship Scales Questionnaire (RSQ) is a multidimensional construct with nine factors: “dismissing,” “preoccupied with romance,” “preoccupied with close relationships,” “fearful,” “preoccupied with dependency,” “secure emotional,” ”comfortable depending,” “preoccupied with mistrust” and “mutual secure.” Different attachment styles were positively or negatively correlated at a significant level with perceived stress and social support. Attachment styles were explained by 20 and 33% of the total variance in self-perceived stress and perceived social support, respectively. There were significant gender, ethnic and religious differences in attachment styles, perceived stress and social support.